MODELLING AND SIMULATION OF WATER GAS SHIFT REACTOR USING COMSOL MULTIPHYSICS - SOIT, Adrian Catalin; DUMBRAVĂ, Ionela; SANDU, Vlad-Cristian; CORMOS, Ana-Maria (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Hydrogen production from fossil fuels plays an important role in the global H2 demand. In general, H2 production from fossil sources implies syngas generation, typically by gasification or reforming, followed by the water gas shift process. The aim of this work is to determine the behaviour of the water gas shift process (in a packed bed reactor) through modelling and simulation using COMSOL Multiphysics software. In the developed model, diffusion is the main type of transport of the chemical substances. The challenges are to model the complex phenomena associated with a multiscale system: a macroscale level in the macropores between the dumped catalyst particles and a microscale level, inside of the pellets’ micropores.